2009
DOI: 10.1111/j.1538-7836.2009.03302.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biomarkers, hormone therapy and the risk of venous thromboembolism in women

Abstract: To cite this article: Everett BM, Glynn RJ, Buring JE, Ridker PM. Lipid biomarkers, hormone therapy and the risk of venous thromboembolism in women. J Thromb Haemost 2009; 7: 588-96.Summary. Background: Published reports of a relationship between lipids and incident venous thromboembolism (VTE) are conflicting. Objectives: To clarify the relationship between lipids and VTE risk in healthy women, including potential effect modification by hormone therapy (HT). Patients/methods: Among 27 081 initially healthy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
4
32
1
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12] In our analysis we found no significant association between physical activity (metabolic equivalents/week) and the risk of idiopathic pulmonary embolism. In addition, the increased risk of pulmonary embolism associated with physical inactivity was more apparent in women with lower levels of physical activity.…”
Section: Comparison With Other Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12] In our analysis we found no significant association between physical activity (metabolic equivalents/week) and the risk of idiopathic pulmonary embolism. In addition, the increased risk of pulmonary embolism associated with physical inactivity was more apparent in women with lower levels of physical activity.…”
Section: Comparison With Other Studiesmentioning
confidence: 83%
“…Arterial and venous thrombosis share multiple risk factors such as obesity, cigarette smoking, and hypertension. [4][5][6][7] Associations between physical inactivity, physical activity, and pulmonary embolism remain uncertain. Some published case-control studies found that exercising on a regular basis decreases the risk of venous thrombosis by 30-50% compared with not exercising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The results of the present study, along with other recently published prospective studies on this topic, [32][33][34] emphasize the need of an updated systematic review.…”
Section: Braekkan Et Al Risk Factors For the Competing Risk Of MI Andmentioning
confidence: 89%
“…29,30,35 Nevertheless, in three large cohort studies [36][37][38] investigators reported no association between HDL cholesterol and VTE and a tendency toward a greater risk of unprovoked VTE in women. In the present study, patients with VTE had similar baseline HDL cholesterol as healthy controls, whereas total HDL particle concentration was greater both in the fasting and postprandial state (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 98%